Implementation of Oral Hygiene with Propolis to Prevent Ventilator-Associated Pneumonia in Mechanically Ventilated ICU Patients - Nadira Jihan Fitria; Enita Dewi; Fila Diana Nurhayati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Ventilator-associated pneumonia (VAP) merupakan komplikasi serius yang dapat terjadi pada pasien yang menggunakan ventilator mekanik di unit perawatan intensif (ICU). Oral hygiene is a vital nursing intervention that reduces oropharyngeal colonization and the risk of VAP. Propolis, a natural substance having antibacterial and anti-inflammatory qualities, has been suggested as a substitute for chlorhexidine, which has been linked to side effects. This paper describes the implementation of evidence-based oral hygiene using a propolis solution as part of nursing care for mechanically ventilated patients, with the aim of supporting infection prevention and maintaining clinical stability. Four ICU patients who had been on mechanical ventilation for over 48 hours received oral care using pure propolis diluted in sterile distilled water, administered twice daily for three days. The patients’ conditions were monitored through the Beck Oral Assessment Scale (BOAS), the Modified Clinical Pulmonary Infection Score (MCPIS), and the Acute Physiology and Chronic Health Evaluation II (APACHE II). BOAS scores demonstrated improved oral hygiene, while MCPIS values declined, indicating reduced VAP risk. APACHE II assessments suggested stabilization of disease severity. No adverse effects were observed, confirming the safety and feasibility of the intervention in critical care practice. The implementation of oral hygiene with propolis solution, grounded in evidence-based nursing practice, proved to be a safe and practical intervention. Beyond improving oral conditions, it may contribute to VAP prevention and highlights the role of nurses in integrating natural-based, patient-centered strategies into ICU care.